The Effectiveness of Group Counseling with Role Play Techniques to Improve Student Emotional Intelligence - Rismi, Ridho; Yustiana, Yusiriska; Budiman, Nandang (Jurnal Aplikasi IPTEK Indonesia, 2020)
Many people believe that the success of one's life is largely determined by the intelligence of reason. Though the success of one's life is influenced by various factors, one of which is emotional intelligence. Group guidance service is an excellent service to provide awareness to individuals about various healthy behaviors and problematic behavior. Role play is a technique of providing guidance to a group of individuals as a solution to solving individual psychological and social problems through dramatization activities. Where each individual is required to be able to play a certain role in the situation planned by the supervisor adjusted to the purpose of providing guidance to be achieved. Emotional intelligence is formed through five skills namely recognizing one's emotions, managing emotions, motivating yourself, recognizing the emotions of others and building relationships. These five skills are used as benchmarks for understanding one's emotional intelligence. Emotional intelligence is very important in our lives, both inward nature and in relation to other people or situations because it will affect our behavior. With the guidance of the group is expected to provide a good impact on emotions so that it will bring positive behaviour.